IMPLEMENTASI PLATFORM MERDEKA MENGAJAR DALAM MENINGKATKAN KUALITAS PELAYANAN PENDIDIKAN TINGKAT SMP DI KABUPATEN SUMEDANG - irma hermayanty; Aqil Septian Setiadi; Bunga Meidy Aprilia; Dini Aulia; Eva Sri Rohaeni; Rachmawati Bela Putri; Tony Abdul Mugni (LPPM UNSAP & FISIP UNSAP, 2023)
This study aims to examine the implementation of the use of the Merdeka Mengajar Platform on the quality of education services at the junior high school level at the Sumedang District Education Office which is implemented in Sumedang District. The method used in the preparation of this research report is a qualitative method with a descriptive type. The sampling technique used ispurposive sampling, with research informants: Head of Middle School Education Sector, Head of Middle School Curriculum and Student Affairs, Educators for the curriculum section of SMP Negeri 1 Cimalaka Sumedang, and educators for the curriculum for SMP Negeri 9 Sumedang Data collection techniques through library research and field studies, namely by observing, interviewing, and documenting. Based on the results of interviews, observations, and documentation, data analysis was then carried out and it was concluded that the use of the Merdeka Mengajar Platform at the Sumedang Regency Middle School level itself was still not optimal, however, the Sumedang Regency Education Office was swift in handling the problem regarding this PMM complaint and outreach PMM regularly and well.